Marriage, divorce and coronavirus—theoretical analysis of the influence of COVID-19 on family capital - Malaczewska, Paulina; Malaczewski, Maciej (Economics and Business Review, 2022)
The purpose of this paper is to provide the framework to analyze the impact of shocks related to the COVID-19 pandemic on the level of divorce. The model takes into account family/marriage capital with its depreciation, investments in this capital and the costs of divorce. The problem faced by the agent is analyzed and formulas for the optimal division of income between consumption and investments in family capital are derived. Comparative statics is performed by calculating the signs of all derivatives of all variables with respect to all parameters. The analysis shows that a change in economic conditions has the least effect of any factor influenced by COVID-19 in changing the probability of a divorce. To the best of the authors’ knowledge this is the first mathematical model in the literature that covers the issues of the impact of a lockdown on the durability of marriages.